An Overview Of Buckling And Imperfection Of Cone-Cylinder Transition Under Various Loading Condition - Ifayefunmi, Olawale Friday; Ismail, Mohd Shahrom (Brazilian Association of Computational Mechanics, 2020)
The current paper presents a brief survey of literature relevant to buckling of cone-cylinder intersection under different loads such as (i) internal pressure, (ii) external pressure, and (iii) axial compression. The paper explores the up-to-date knowledge on the buckling of cone-cylinder intersection and highlights the areas of gap in knowledge. This is aimed at contributing to better understanding of the relevant issues such as the influence of different types of imperfections in updating the current design guideline that is found to be vital in industrial practice. The review is thematically divided into: (i) the methods adopted in the past work (i.e., how the data were obtained, type of material used, type of design with/without reinforcement), (ii) the highlight and importance of past findings, (iii) the sensitivity to imperfection and its design implications and (iv) the current design recommendation and guidelines. Finally, the current paper provides a brief state-of-the-art and presents an update of related works for the future establishment of shells design guidelines.